Established and emerging GABAA receptor pharmacotherapy for epilepsy - Richardson, Robert J.; Petrou, Steven; Bryson, Alexander (Frontiers in Pharmacology, 2024)
Drugs that modulate the GABAA receptor are widely used in clinical practice for both the long-term management of epilepsy and emergency seizure control. In addition to older medications that have well-defined roles for the treatment of epilepsy, recent discoveries into the structure and function of the GABAA receptor have led to the development of newer compounds designed to maximise therapeutic benefit whilst minimising adverse effects, and whose position within the epilepsy pharmacologic armamentarium is still emerging. Drugs that modulate the GABAA receptor will remain a cornerstone of epilepsy management for the foreseeable future and, in this article, we provide an overview of the mechanisms and clinical efficacy of both established and emerging pharmacotherapies.